Characteristics of Presbyopia Patients at Eye Health Center Makassar - Naufal Asy’ Ari Nur; Purnamanita Purnamanita; Irwandi Rachman (Universitas Islam Negeri Alauddin Makassar, 2021)
Presbyopia is a visual disorder related to age. It occurs lens stiffness with adding the age in presbyopia in order to lens ability to focus shadow when looking can be near. This research aimed to know the characteristics of presbyopia patients at eye health center Makassar in the period of January-December 2018. The research design is a descriptive study using secondary data. The number of samples in this study were 97 medical record data selected by purposive sampling and analyzed by univariate and bivariate. The results showed that as many as 97 patients, the majority were 64 women (34%), the majority of the presbyopia were at the age of 40-45 years as many as 23 people (23.7%). Based on the characteristics of the presbyope patient, there were 48 patients (49.5%) suffering from hypermetropic presbyopia, while 18 patients (18.5%) suffered from other presbyopes such as premature presbyopia (early). It is hoped that the provision of information about presbyopia can be scientific support for the optometrist practice program.